Kualitas pengiriman dan loyalitas pelanggan GoFood: Peran mediasi kepuasan pelanggan - Hendrick Hernando; Jati Nugroho (Universitas Kristen Maranatha, 2022)
Delivery quality discussion in the online food studies received scarce attention. This study examines the direct effect of delivery quality on customer loyalty and its indirect through customer satisfaction as mediating variable. A total of 125 GoFood customers in Madiun participated in this study. By applying Partial Least Squares (PLS) technique to evaluate the conceptual model, this study confirms the indirect effect of delivery quality on loyalty, but not the direct effect. The PLS results indicate the full mediation role of customer satisfaction on the link between delivery quality and customer loyalty. Past studies have mainly focused on the quality of ordering apps in the online food delivery context. This study provides an understanding of delivery quality roles in the current online food studies. Finally, this study informs service providers to ensure on-time delivery in creating their customer loyalty.